Odpowiedzi

2010-03-02T23:28:59+01:00
A) -2-2*5= -2-10=-12
b) (-8):4-2=-2-2=-4
c) 12:(-2)-(-3)= -6+3=-3
d) (-2) do potęgi3 * 3 - 25= -8*3-25=-24-25=-49
e) (-15):3-5*(-1)= -5+5=0
f) 3* (-7) -7 * (-2)=-21+14=-7
g) 6* (-4) + 5* (-9)=-24-45=-69
h) (-18):9-(-27):(-1)=-2-27=-29
2010-03-02T23:33:05+01:00
A) -2-2*5 = -4*5= -20
b) (-8):4-2 = -2-2= -4
c) 12:(-2)-(-3) = -6+3= -3
d) (-2) do potęgi3 * 3 - 25 = -8*3-25 = -24-25- = -49
e) (-15):3-5*(-1) = -5 - 5 = 0
f) 3* (-7) -7 * (-2) = -21 + 14 = 7
g) 6* (-4) + 5* (-9) = -24 - 45 = -69
h) (-18):9-(-27):(-1) = -2 + 27 = 25

jeżeli popełniłam gdzieś błąd to przepraszam